The Functional Slots of Finite Verb Tagmas - Muhartoyo, Muhartoyo (Bina Nusantara University, 2012)
Tagmemic analysis is a comprehensive language analysis introduced by Prof. Kenneth L. Pike and Evelyn G. Pike from the Summer Institute of Linguistic, USA. This analysis enables linguists to study a language, especially the one which has not been studied before, in a more comprehensive manner. This study attempts to reveal functional slots that be filled by finite verb tagmas in English. The data for this study were taken from various published printed media which have high standard English. Ten different sentences were selected to be analyzed using Tagmemic analysis. Slot-role and four-cell analysis were conducted in this study. The result of analysis shows that Predicate Slot in English must be filled by finite verb tagmas. As the predicate is the essential or obligatory element in a clause construction, the ability to identify the occurrence of finite verb tagmas in English is compulsory. Finite verbs tagmas have different roles depending on the type of clauses. Tagmemes following the Predicate slots also vary depending on the transitivity of the finite verbs.